Proteasome stress activates YAP/TAZ through the RAP2–MAP4Ks–LATS1/2 pathway and its therapeutic implications in solid tumors - Xin Wang; Yuan Gu; Zhenxing Zhong; Pengcheng Yu; Wenshuai Liu; Rui Zhu; Yu Wang; Zhaocai Zhou; Yihong Sun; Xuefei Wang; Fa-Xing Yu (Proceedings of the National Academy of Sciences, 2025)
Tumor cells heavily depend on proteasome-mediated protein turnover, making the proteasome an attractive therapeutic target. Clinically, proteasome inhibitors are effective against hematologic cancers but show limited success with solid tumors, and the reasons for this difference are not well understood. Activation of yes-associated protein (YAP)/TAZ, the downstream effectors of the Hippo pathway, is a key mechanism behind drug resistance in cancers. Here, we demonstrate that proteasome stress acts as an upstream signal of the Hippo pathway in solid tumor cells. When the proteasome is inhibited, RAP2 undergoes ubiquitination and becomes inactive, which in turn disrupts the RAP2–MAP4Ks–NF2–LATS1/2 signaling pathway, leading to the activation of YAP/TAZ. YAP/TAZ activation promotes cell survival and resistance to proteasome inhibitors. Conversely, blocking YAP/TAZ can overcome this resistance and restore cancer cell sensitivity to these drugs. In diffuse-type gastric cancer—an aggressive solid tumor with a poor prognosis and limited treatment options—combined inhibition of the proteasome and YAP/TAZ effectively suppresses tumor growth. Therefore, this study identifies proteasome stress as an upstream signal of the Hippo pathway and provides a mechanistic basis for combination cancer therapy.